Um lugar sem lugar... no rock português - Guerra, Paula (2020)
In this article we analyze the reasons for female invisibility in Portuguese rock as a central aspect in the construction of the femininity of the Portuguese contemporaneity. Elsewhere we showed the existence of a consistent male domination in Portuguese rock scene. It seems that the women are barely remembered through the dominant stereotypes lenses, such as mere lovers, companions and submissive social actresses in public space. To combat this invisibility, we propose, first, a state of the art about gender and youth studies, then a brief presentation of the state of female participation in Portuguese rock, and then the central issue of the article: the life history of Xana, vocalist of Radio Macau. A paradigmatic trajectory not only of Portuguese music, but of the entire construction of femininity in the world of arts and culture in recent Portuguese history. ES: En este artículo analizaremos las razones de la invisibilidad femenina en el punk portugués. En otras partes demostramos la existencia de una profunda misoginia en las letras punk portuguesas. Parece que las mujeres solo son recordadas a través de la lente de los estereotipos dominantes, o como meras novias, chaperonas y actores sociales sumisos en el espacio público. Para combatir este olvido, proponemos, primero, un estado del arte que cruza los estudios de género y juventud, luego una breve presentación del estado de la participación femenina en el rock portugués, y luego nos centramos en el tema central del artículo: la historia de vida de Xana, la vocalista de Rádio Macau. Una trayectoria paradigmática no solo de la música portuguesa, sino de toda la construcción de la feminidad en el mundo de las artes y la cultura en la historia portuguesa reciente.